Assessment of the performance of pervious concrete in the removal of contaminants in wastewater - Defensor, Rea Ann S.; Samonte, Louis Isaac I.
Pervious concrete is a type of material that allows water to pass through. Because of this, pervious concrete is known to be used as a flood control measure. Another application of pervious concrete is to remove contaminants present in water. Previous studies have shown that pervious concrete can decrease acidity, salinity, and oil content (Lee et. al, 2014). The study determined how effective pervious concrete is in removing various contaminants present in wastewater samples. The importance of this study is that, since polluted water can affect the bodies of water receiving it, surface water or groundwater, it is important to have technologies that will reduce contaminants levels in the water. The study looked into the difference between the contaminant concentrations before and after passing through the concrete sample. It also studied how the properties of pervious concrete affected its performance in contaminant removal. Also, it observed how the exposure to water samples affects the contaminant removal efficiency and the compressive strength of the pervious concrete. The wastewater was passed through the pervious concrete sample and the difference between the contaminant concentration levels before and after passing through the concrete was obtained. After the single pass-through, the concrete specimens were immediately tested for the multiple pass-through by means of recirculating the effluent water from the preceding pass. Statistical analysis was conducted in order to know if the changes in concentration were significant. Pervious concrete was able to decrease turbidity in water by as much as 35%, and total suspended solids by as much as 38%. There was no significant change in terms of total dissolved solids, although the value generally decreased. The amount of phospate in the water significantly decreased by as much as 11%, while the nitrate increased in concentration. One possible reason is that the materials for concrete preparation were contaminated before mixing. There were significant differences between varying maximum aggregate size and amount of fine aggregates in the mix for turbidity, pH, and total dissolved solids.Multiple pass-through present up to 3rd pass. Also, it was observed that in some test cases, significant change in the concentrations do not happen until the 3rd pass.